CASE STUDY ON THE EFFECT OF ALTERNATE NOSTRIL BREATHING EXERCISE (ANBE) ON VITAL SIGNS IN HEART FAILURE PATIENTS - Yusmita Puji Lestari; Akhyarul Anam; Aprilia Kartikasari (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
Introduction: Heart failure is commonly a major cause or significant contributor to mortality. Due to this condition, heart failure patients generally experience hemodynamic instability, which is typically managed with pharmacological therapy. However, to balance the side effects of pharmacological treatments, heart failure patients also need complementary modalities that can help restore hemodynamic stability, one of which is a breathing exercise therapy known as Alternate Nostril Breathing Exercise (ANBE). Purpose: To evaluate the implementation of Evidence-Based Practice by analyzing the effect of Alternate Nostril Breathing Exercise (ANBE) on blood pressure, pulse rate, respiratory rate, and oxygen saturation in heart failure patients. Methods: The design of this scientific paper is a descriptive case study with nursing care approach for patients with heart failure. The study involved two respondents with heart failure, both experiencing shortness of breath as the main complaint. Interventions were provided twice daily for 10 minutes over a period of 5 days. evaluation is carried out formatively and summatively. Discussion: The ANBE intervention resulted in a decrease in blood pressure, MAP (mean arterial pressure), and respiratory rate, as well as an increase in oxygen saturation in both patients. As for the pulse rate, results tended to be stagnant when comparing pre- and post-intervention measurements within a single day; however, a decrease was observed when comparing measurements taken before the intervention and on the final day of the intervention. Conclusion: ANBE therapy contribute in lowering blood pressure, MAP, and respiratory rate, also improve oxygen saturation.